Music teacher education for primay and secondary schools in Switzerland - Epelde Larrañaga, Amaya (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
Switzerland is considered as a country with a ri ch cultural tradition which, at the same time, takes care of the people’s professional training in any branch. Notwithstanding, regarding music in compulsory education, there is a poor presence, so we have wondered what the music teacher education is like in that country. This paper pursues to inform about the music teacher education programme. We will also refer the current status of this field in Spain, discussing the lessons we can take for our country and, by and large, for the training of pre-service music teachers